2017
DOI: 10.1080/00048402.2017.1399151
|View full text |Cite
|
Sign up to set email alerts
|

Logical Pluralism from a Pragmatic Perspective

Abstract: This paper presents a new view of logical pluralism. This pluralism takes into account the way the logical connectives shift depending on the context in which they occur. Using the Question-Under-Discussion Framework as formulated by Craige Roberts, I identify the contextual factor which is responsible for this shift. I then provide an account of the meanings of the logical connectives which can accommodate this factor. Finally, I suggest that this new pluralism has a certain Carnapian flavor. Questions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Their paper provides a sharp and elegant characterization of metainferential validity and their main result allows us to translate the question of whether some metainference holds in ST + into a question about whether some related inference holds in LP + . 16 In addition to this, Barrio, Rosenblatt and Tajer take the results in their paper to argue for two claims (these claims appear intertwined in the paper): Claim 1: That, contrary to what it is claimed in Cobreros et al [9], ST + is not classical logic.…”
Section: Lp + In Sheep's Clothing?mentioning
confidence: 96%
See 1 more Smart Citation
“…Their paper provides a sharp and elegant characterization of metainferential validity and their main result allows us to translate the question of whether some metainference holds in ST + into a question about whether some related inference holds in LP + . 16 In addition to this, Barrio, Rosenblatt and Tajer take the results in their paper to argue for two claims (these claims appear intertwined in the paper): Claim 1: That, contrary to what it is claimed in Cobreros et al [9], ST + is not classical logic.…”
Section: Lp + In Sheep's Clothing?mentioning
confidence: 96%
“…Barrio et al [4] suggest that it requires us to endorse logical pluralism. We take no stand here on the debate around logical pluralism (see eg [6,16,24]). But whether or not logical pluralism is correct, it would certainly be awkward if we were forced, merely by our advocacy of ST + , also to advocate logical pluralism.…”
Section: Making Sense Of Barrio Et Al's Desideratummentioning
confidence: 99%
“…Most of them rely on relativising the normatively relevant logic to some plausible parameter. Some authors choose this parameter to be the context [Caret, 2017;Kouri Kissel, 2018], some choose it to be the epistemic goal or purpose [Blake-Turner and Russell, 2021], and yet other choose it to be the domain of inquiry (physics, economics, etc.) [Hjortland, 2017].…”
Section: The Collapse Argumentmentioning
confidence: 99%
“…Guest Editors: H. Antunes and D. Szmuc various different kinds of truth bearers [Russell, 2008]. Others have suggested that there is a plurality of correct logics because there are various legitimate choices as to which are the logical constants of natural language [Varzi, 2002], or alternatively, various ways to make precise the meaning of these constants [Kouri Kissel, 2018]. Finally, some authors have claimed that there is a plurality of correct logics because there are various ways to make precise the meaning of the vernacular predicate "follows deductively from" [Beall and Restall, 2006;Cook, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Trying to understand a discipline from different scientific values is a new way to do, which can make stronger interdisciplinary and transdisciplinary approaches. Bringing back analytic philosophy and other philosophical schools discussions into the framework of the pluralist spirit emerging lastly in science and logic [74,75] is relevant for building a new analysis, and should no longer be an elitist dialogue, but a relevant one with a wide participation of the scientific community.…”
Section: Wide Knowledge Discovery Strategy Towards Aa Paradigm: Philosophical Cognitive and Strategic Argumentsmentioning
confidence: 99%